The Influence of Green Accounting and Intellectual Capital on Firm Value with Business Strategy as a Moderating Variable - Hana Agustin; Noer Sasongko (Transpublika Publisher, 2026)
Investor perceptions of corporate performance, as captured by firm value, are determined by financial considerations alongside non-financial dimensions, namely environmental responsibility management via green accounting and the strategic utilization of intellectual capital to secure competitive advantage. This study assesses the extent to which green accounting and intellectual capital affect firm value, while also considering the moderating role of business strategy. The analysis focuses on mining firms listed on the Indonesia Stock Exchange from 2021 to 2024, utilizing secondary data derived from annual reports through purposive sampling according to explicit selection criteria. Methodologically, the investigation applies a quantitative approach, implementing both multiple linear regression and Moderated Regression Analysis (MRA) for hypothesis testing. The results indicate that green accounting and intellectual capital each have a statistically significant impact on firm value. Nevertheless, business strategy is unable to moderate the influence of either green accounting or intellectual capital on firm value, and consequently, no moderating role is substantiated. The study aims to contribute to corporate value enhancement strategies and to provide a foundation for future scholarly inquiry.